Hubungan Attachment Antara Anak dan Ibu yang Bekerja terhadap Perkembangan Sosial Emosional Anak Usia Dini di TK Aisyiyah Bustanul Athfal 22 Surabaya - Lutfiah Zahra; Gunarti Dwi Lestari (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Mothers have an important role and become the main in forming attachments with children. The condition of working mothers allows for lack of time with children, impacting the attachment relationship between mother and child. The quality of the attachment between mother and child will impact the child's social-emotional development. This study aims to determine whether there is a relationship between the attachment of children and working mothers to the emotional and social development of early childhood at TK Aisyiyah Bustanul Athfal 22 Surabaya. This research was conducted using a quantitative approach to the type of correlational research. The data analysis used is Product Moment correlation analysis. The number of respondents in this study was 32 working mothers who had children aged 4-6 years. Data collection techniques used are questionnaires, observation, and documentation. The study's results showed a correlation of 0.537 which means that there is a relationship between child attachment and working mothers on children's social-emotional development.